EVOLUSI MANAJEMEN KEUANGAN SYARIAH: PERKEMBANGAN PADA ZAMAN RASULULLAH SAMPAI SEKARANG - Sultoni, Hasan (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2017)
Shariah financial management is an activity of planning, management, controlling, financial examination based on sharia principles based on al-Qur'an and al-Hadith. Activity use of funds based on Islamic sharia principles must have existed since the time of the Prophet. All collection of state assets must be collected first and then issued according to the needs of the state. Along with the development of the time of financial management activities emerged the latest innovations so as to facilitate the understanding of sharia-based finance to the public. The development of rapid financial management is not only driven by religious spirit in implementing Islamic teachings, but also motivated by pragmatic practical interests in building the economy of the ummah.